Potensi Toksin Binders untuk Mengurangi Efek Mikotoksin Zearalenon terhadap Panjang, Bobot, dan Jumlah Fetus Mencit (TOXIN BINDERS HAS THE POTENTIAL TO DECREASE ZEARALENONE MYCOTOXIN ON FETAL LENGTH, WEIGHT AND LITTER SIZE OF PREGNANT MICE) - Purnama, Muhammad Thohawi Elziyad; Saputro, Amung Logam; Prastiya, Ragil Angga (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Corn is a source of feed with protein content to increase livestock production. Zearalenone is a mycotoxin produced by Fusarium graminearum obligate in corn. The mycotoxins allegedly can cause pregnancy disorders to fetal malformations. Using toxin binders to inhibit zearalenone mycotoxins. The purpose of this study was to determine the potential of toxin binders in reducing the effect of zearalenon on the length, weight and fetal litter size of pregnant mice (Mus musculus). This study used 20 balb/c mice divided into control group (C-) without toxin binders and zearalenone; (C+) was given only zearalenone 0.1 mg / mice / day; and treatment groups T1; T2; T3 was given zearalenone 0.1 mg / mice / day and toxin binders 0.5; 1; 2 mg / mice / day. The toxin binders and zearalenone was done with orally for 14 days. The data were analyzed using Analysis of variance test and continued by Duncan test. The results showed that C-, C+, T1 were significantly different (p<0.05) with T2 and T3 on the fetal length. The fetal weight showed C-, T1, T2, T3 was significantly different (p<0.05) with C+. The result of fetal litter size showed that were not significantly different (p>0.05) between treatment groups. It was concluded that toxin binders could decrease the effect of zearalenon thus increasing the length and weight of the fetus but not affecting the fetal litter size of pregnant mice (M. musculus).